2021
DOI: 10.1101/2021.04.22.441042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Two-Component System FleS/FleR Regulates Multiple Virulence-Related Traits inPseudomonas aeruginosa

Abstract: Microorganisms commonly use two-component systems (TCSs) to detect specific environmental changes and respond accordingly for their own benefit. However, the regulatory mechanisms and physiological roles of a majority of TCSs are still elusive. In this study, we focused on a previously predicted TCS FleS/FleR in Pseudomonas aeruginosa to systematically investigate its regulation and physiological roles. Loss of fleS or fleR or both genes led to decreased biofilm formation and attenuated motility in PAO1, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Additionally, it has been reported that FleQ is related to the regulation of the cdrAB gene, which encodes for adhesin, which in turn is necessary for the early stages of P. aeruginosa bio lm formation (Baraquet and Harwood 2016). The eR gene encodes for the FleR protein, which forms a two-component FleS/FleR system to control P. aeruginosa bio lm formation and motility (Zhou et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that FleQ is related to the regulation of the cdrAB gene, which encodes for adhesin, which in turn is necessary for the early stages of P. aeruginosa bio lm formation (Baraquet and Harwood 2016). The eR gene encodes for the FleR protein, which forms a two-component FleS/FleR system to control P. aeruginosa bio lm formation and motility (Zhou et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The statistically significant increase of pseudobactin 358 production in Δ rclS mutant indicates the negative regulation of its production mediated by sensor kinase RclS. Previously, the role of FleS/FleR TCS in siderophore biosynthesis regulation in P. aeruginosa was described [ 37 ]. Moreover, this TCS regulates the secretion systems in P. aeruginosa [ 37 ], and a similar result has been obtained by KEGG analysis for RclSAR system of WCS358 in the stationary phase of growth.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the role of FleS/FleR TCS in siderophore biosynthesis regulation in P. aeruginosa was described [ 37 ]. Moreover, this TCS regulates the secretion systems in P. aeruginosa [ 37 ], and a similar result has been obtained by KEGG analysis for RclSAR system of WCS358 in the stationary phase of growth. This observation, as well as the results obtained from the cytotoxicity and adhesion tests performed on the keratinocyte cell line, indicates the role of RclS in P. capeferrum WCS358 virulence potential.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 19 , 20 Class III genes, responsible for the formation of the flagellar hook and rod, fall under the control of FleSR. 17 , 21 , 22 Homologs of FleSR have been identified in other flagellated bacteria such as Vibrio cholera (FlrBC), Shewanella oneidensis (FlrBC), Campylobacter jejuni (FlgSR), and Helicobacter pylori (FlgSR). 23 , 24 , 25 , 26 , 27 Mutants of fleS or fleR are non-motile and significantly less virulent in P. aeruginosa .…”
Section: Introductionmentioning
confidence: 99%